Ideological functions and national interests in the journalism - Ashirbayev Б.Т. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2020)
New and old are merging in the domestic information space. We are abandoning the paper culture in print and moving to an electronic culture. Global trend. In the formation of the world image of independent Kazakhstan, the importance of domestic journalism is increasing, its essence and content are changing, and its character is changing. We need to strengthen our legal position, which guarantees freedom of the press, and ensure transparency of financial sources. The article analyzes the prospects of the national information space, comprehensively examines the issues of political and ideological activities of journalism, the specifics of the profession. The significance of studying is explained for the specialty «international journalism» at the University